TEXT CENTRIC APPROACH TO THE DEVELOPMENT OF SPEECH, EXPRESSION OF THE FUTURE TUTORS OF PRESCHOOL EDUCATION THEORY AND METHODS OF TEACHING - Rudenko, Yulia А. (Educological discourse, 2015)
The article is devoted to methodological rationale of the use of text centric approach in the development of speech, expression of future nursery-teachers’. The author reveals the importance of the key concepts of text centric approach: the cultural importance of professionally oriented texts (KSPOT), the cultural significance of a professional discourse.